Debris Flow Detection by Combinations of LVP Sensors and Wires: Examples in Sakura-jima Island in Japan - Takahiro Itoh; Satoshi Tagata; Takahisa Mizuyama (Journal of the Civil Engineering Forum, 2024)
Various kinds of sensors for debris flows detection have been proposed such as wire sensor, acceleration sensor, and so on. In Europe, a geophone that is based on a vibration meter is usually used though the applicability is not confirmed for debris flow detection in Japan. A wire sensor is still currently used for debris flow detection in Japan, because of its easy maintenance and measurement principle of disconnected wires. However, there is a drawback in that debris flow cannot be detected until manual maintenance is performed after the wires are disconnected. Sakura-jima is in southwest of Japan. Debris flows occur by rainfall and ash fall after eruption. Many debris flows occur and transport sediment by debris flow events. The number of debris flow occurrences is defined by the number of disconnected wires from a wire sensor, and three wires are set vertically at the height of 60 cm, 120 cm, 180 cm from the bed, respectively, to know magnitude of debris flow height. A LVP sensor has been developed and installed there for continuous detection of debris flows and modified based on technical information obtained by maintenance after debris flow events. The sensor consists of load cell (L), acceleration meter due to vibration (V) and pressure meter (P). The sensor is mainly for debris flow detection, though weight of debris flows on the bed is attempted to be measured using a small box with loadcell. Present studies introduce some examples of debris flow detections using the LVP and emphasize usage of the LVP sensor in combination with wires.